Hsa_circ_0040809 and hsa_circ_0000467 promote colorectal cancer cells progression and construction of a circRNA-miRNA-mRNA network - Liu, Jingfu; Chen, Shan; Li, Zhen; Teng, Wenhao; Ye, Xianren (Frontiers in Genetics, 2022)
Abstract Objective: Circular RNAs (circRNAs) have been demonstrated to be closely involved in colorectal cancer (CRC) pathogenesis and metastasis. More potential biomarkers are needed to be searched for colorectal cancer (CRC) diagnosis and treatment. The objective of this study is to seek differentially expressed circRNAs (DEcircRNAs), test their roles in CRC and construct a potential competing endogenous RNA (ceRNA) network. Methods: CircRNA microarrays were obtained from Gene Expression Omnibus, and differential expression was analyzed by R software. The relative expressions of DEcircRNAs were confirmed in CRC tissues and cell lines by qRT-PCR. MTs and Transwell experiment were used for detecting the roles of DEcircRNAs on CRC cell proliferation and migration, respectively. Targeted miRNAs of circRNAs and targeted mRNAs of miRNAs were predicted and screened by bioinformatics methods. A competing endogenous RNA (ceRNA) network of DEcircRNAs was constructed by Cytoscape. To further verify the potential ceRNA network, the expressions of miRNA and mRNA in siRNA of DEcircRNAs CRC cells were detected by qRT-PCR. Results: Two DEcircRNAs (hsa_circ_0040809 and hsa_circ_0000467) were identified and validated in CRC tissues and cell lines. The results of MTs and Transwell experiment showed that hsa_circ_0040809 and hsa_circ_0000467 promote CRC proliferation and migration. Bioinformatics analysis screened 3 miRNAs (miR-326, miR-330-5p, miR-330-3p) and 2 mRNAs (FADS1 and RUNX1), and a ceRNA network was constructed. In knockdown of hsa_circ_0040809 HCT-116 cells, the expression of miR-330-3p was significantly upregulated, while RUNX1 was significantly downregulated. In knockdown of hsa_circ_0000467 HCT-116 cells, the expressions of miR-326 and miR-330-3p were upregulated, while ELFN1was downregulated. Conclusion: We found that hsa_circ_0040809 and hsa_circ_0000467 were upregulated in CRC tissues and cell lines, and promote CRC cell progression. A circRNA-miRNA-mRNA network based on hsa_circ_0040809 and hsa_circ_0000467.